2012
DOI: 10.1038/sc.2011.189
|View full text |Cite
|
Sign up to set email alerts
|

Heart adaptations to long-term aerobic training in paraplegic subjects: an echocardiographic study

Abstract: Study design: Case-control. Objectives: To execute an echocardiographic comparison between trained and untrained spinal cord injury (SCI) subjects, and to evaluate whether long-term heart adjustments to endurance training are comparable to those observed in able-bodied (ABL) subjects. Setting: Italy. Methods: We enrolled: (1) 17 male SCI patients (lesion level T 1 -L 3 , 34±8 years, body mass index (BMI) 23.0±2.8 kg m À2 ), 10 of whom were aerobically trained for 45 years (SCI T ); (2) 18 age-, sex-and BMI-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
9
1
4
Order By: Relevance
“…Furthermore, the observed reduction in LVIDd demonstrated by the spinal cord injured participants is in agreement with several previous reports. [10][11][12]28 However, the commonly reported reduction in LVM in this population [8][9][10]28,29 was not observed in the current participants. As mentioned, the smaller LVIDd can be explained by the chronic reduction in preload, as demonstrated by a lower end-diastolic volume and blood volume.…”
Section: Structural and Hemodynamic Findingscontrasting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, the observed reduction in LVIDd demonstrated by the spinal cord injured participants is in agreement with several previous reports. [10][11][12]28 However, the commonly reported reduction in LVM in this population [8][9][10]28,29 was not observed in the current participants. As mentioned, the smaller LVIDd can be explained by the chronic reduction in preload, as demonstrated by a lower end-diastolic volume and blood volume.…”
Section: Structural and Hemodynamic Findingscontrasting
confidence: 65%
“…[11][12][13][14] It has been proposed that the chronic physical inactivity after SCI may have a role in such diastolic impairments, as active spinal cord injured individuals have been shown to present better diastolic patterns compared with sedentary ones. 11,14 However, Maggioni et al 29 reported no difference in diastolic function between trained and untrained spinal cord injured individuals and De Groot et al 8 reported no difference in diastole between able-bodied individuals and sedentary individuals with severe tetraplegia. In addition, Driussi et al 12 reported lower diastolic function in those with SCI compared with able-bodied individuals even after controlling for levels of physical activity, suggesting that physical activity did not have a major role in the diastolic impairments.…”
Section: Baseline Diastolic Functionmentioning
confidence: 99%
“…Additionally, indices of LV mechanics are sensitive to increases and decreases in sympathetic activity (Weidemann et al, 2002 ; Akagawa et al, 2007 ), which may provide insight into the influence of lesion level on LV performance. Few studies have performed echocardiographic assessments in athletes with SCI (Huonker et al, 1998 ; Gates et al, 2002 ; Schumacher et al, 2009 ; Maggioni et al, 2012 ; West et al, 2012a ; De Rossi et al, 2014 ), with none of these investigations examining LV mechanics. Given evidence that global LV systolic dysfunction is associated with impairments in LV mechanics, and that these functional changes may limit exercise performance, the examination of LV structure, function and mechanics in athletes with SCI may help to elucidate potential factors limiting cardiac responses to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…6 Muscle strength is decreased because neurological input to the affected muscles that retain partial innervation is deficient, leading to the loss of normal activation timing and force-generating capacity. 7 Secondary to the loss of neural inputs are negative musculoskeletal adaptations such as transformation to faster muscle fibers (IIa, IIb) 7 increased contractile speed and increased fatigue in partially paralyzed and also innervated muscles in people with SCI.…”
Section: Rationalementioning
confidence: 99%